Editorial - NAIN, Manjeet Singh (Indian Journal of Extension Education, 2022)
Agricultural Extension services are continuously evolving in India with a focus on productivity and farmers’ livelihood improvement. The agricultural sector has witness a wide range of reforms, but the unsustainable, fragmented and decentralized approach attracted debate and criticism about the effectiveness of sporadic efforts. Need is felt to promote and facilitate innovation and adoption of best farming practices, support rural agriculture commercialization for sustainable development, facilitate agriculture financing and marketing and strengthen the link between farmers, input suppliers and agriculture institutions. Recent pandemic also called for newer and reoriented methodologies for extension services and new opportunities to handle the research issues in experimental as well as exploratory mode. It’s my privilege to present the current issue (October- December, 2021) from cross sectional authors and content ranging from basic research in the form of tool development; gender mapping; nutritional status of children on complementary feeding practices; women participation; pulses related different issues; climatic issues; training effectiveness; economic analysis; entrepreneurial behaviour, conservation technologies and its adoption; social media usages; educational modules; adoption of different technological options in specific agro climatic zones, millet performance; fisheries and dairy related extension issues and so on. The studies reported in the issue represent author and locale of studies from 15 Indian states and union territories. Its more satisfying that authors have reoriented their research issues in light of current situations. Again it is stressed that the scientific reporting need far deeper commitment and more active engagement, I am happy that the readers, authors and reviewers have significantly contributed towards successful implementation. The IJEE is indexed at CAB International; metadata in desirable form is being submitted to Crossref to have wider circulation and opportunity for citations and indexing, hence the authors need to apply more rigor while submitting manuscripts. I extend my sincere thanks to all the authors for making valuable contributions.I also extend sincere thanks to all the expert members in the editorial board (Dr. H. K. De, Dr. Kalyan Ghadei, Dr. Lalita Vatta, Dr. S. S. Dolli & Dr. V.P.S. Yadav) for their painstaking efforts. The support extended by Executive Council is duly acknowledged.Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters.(Manjeet Singh Nain)